Exploring Grief Expression of a Main Character in the A Man Called Otto Movie - Annisa Sofiatun Naza; Afina Murtiningrum (LPPM Universitas Dhyana Pura, 2025)
Grief is recognized as a universal psychological phenomenon, with its manifestation influenced by individual differences and contextual variables such as personality traits, cultural background, and the relational proximity to the deceased (Worden, 2009; Stroebe et al., 2007). The present study investigated the expressions of grief as portrayed by Otto, the protagonist in the film A Man Called Otto (2022). Following the death of his spouse, Sonya, Otto displays a series of emotional and behavioral alterations, including social withdrawal and changes in affective expression. The film serves as a narrative medium through which complex psychological processes, such as bereavement and emotional regulation, are represented. This study employed the Modes of Expression framework proposed by Corless et al. (2009), which classifies grief-related responses into four categories: verbal, non-verbal, physical, and behavioral expressions. A qualitative descriptive method was utilized, with primary data extracted from the film’s narrative and screenplay, and triangulated with secondary sources comprising peer-reviewed articles, psychological texts, and grief-related theoretical literature. Scenes relevant to the portrayal of grief were systematically identified and thematically analyzed in alignment with the established framework. Findings indicated that Otto’s grief is conveyed through a combination of spoken language, silence, facial expressions, and purposeful actions, most notably, repeated visits to his late wife's grave. These behaviors underscore the multifaceted and often non-verbal nature of grief expression. Moreover, Otto’s trajectory from emotional isolation to renewed interpersonal engagement reflects the dynamic and transformative characteristics of the mourning process (Neimeyer, 2001). This study contributed to the growing body of literature on cinematic representations of psychological states, offering insights into how grief may be externalized through narrative structures and character development in visual media.